Innovation management in technology-related knowledge-intensive business services. (18th May 2009) - Ojanen, Ville; Xin, Yan; Chai, Kah-Hin
This paper aims to contribute to the fragmented research fields of service innovation and knowledge-intensive business services (KIBS). On the basis of synthesis of results from extensive literature reviews as well from case studies in technology and engineering consultancies in Singapore, we have been able to develop a framework with propositions for investigating how KIBS, especially technology-related KIBS innovate and how does the internal and external knowledge and typical service characteristics (IHIP) affect service innovation in KIBS firms. Case studies have revealed different types of service innovations as well as enablers and barriers of innovative behaviour in technology-related KIBS and the developed framework as well as detailed hypotheses will be utilised in the future quantitative study for complementing the qualitative data. From the managerial point of view, the results and propositions may provide new insights for technology-related KIBS on how to promote knowledge processing activities and service innovation.